Clinical and Neurophysiologic Phenotypes in Neonates With BRAT1 Encephalopathy. (21st March 2023) - Carapancea, Evelina; Cornet, Marie-Coralie; Milh, Mathieu; De Cosmo, Lucrezia; Huang, Eric J.; Granata, Tiziana; Striano, Pasquale; Ceulemans, Berten; Stein, Anja; Morris-Rosendahl, Deborah; Conti, Greta; Mitra, Nipa; et al.
Abstract : Background and Objectives: BRAT1 encephalopathy is an ultra-rare autosomal recessive neonatal encephalopathy. We delineate the neonatal electroclinical phenotype at presentation and provide insights for early diagnosis. Methods: Through a multinational collaborative, we studied a cohort of neonates with encephalopathy associated with biallelic pathogenic variants in BRAT1 for whom detailed clinical, neurophysiologic, and neuroimaging information was available from the onset of symptoms. Neuropathologic changes were also analyzed. Results: We included 19 neonates. Most neonates were born at term (16/19) from nonconsanguineous parents. 15/19 (79%) were admitted soon after birth to a neonatal intensive care unit, exhibiting multifocal myoclonus, both spontaneous and exacerbated by stimulation. 7/19 (37%) had arthrogryposis at birth, and all except 1 progressively developed hypertonia in the first week of life. Multifocal myoclonus, which was present in all but 1 infant, was the most prominent manifestation and did not show any EEG correlate in 16/19 (84%). Video-EEG at onset was unremarkable in 14/19 (74%) infants, and 6 (33%) had initially been misdiagnosed with hyperekplexia. Multifocal seizures were observed at a median age of 14 days (range: 1–29). During the first months of life, all infants developed progressive encephalopathy, acquired microcephaly, prolonged bouts of apnea, and bradycardia, leading to cardiac arrest and death at a median age of 3.5 months (range: 20 days to 30 months). Only 7 infants (37%) received a definite diagnosis before death, at a median age of 34 days (range: 25–126), and almost two-thirds (12/19, 63%) were diagnosed 8 days to 12 years postmortem (median: 6.5 years). Neuropathology examination, performed in 3 patients, revealed severely delayed myelination and diffuse astrogliosis, sparing the upper cortical layers. Discussion: BRAT1 encephalopathy is a neonatal-onset, rapidly progressive neurologic disorder. Neonates are often misdiagnosed as having hyperekplexia, and many die undiagnosed. The key phenotypic features are multifocal myoclonus, an organized EEG, progressive, persistent, and diffuse hypertonia, and an evolution into refractory multifocal seizures, prolonged bouts of apnea, bradycardia, and early death. Early recognition of BRAT1 encephalopathy allows for prompt workup, appropriate management, and genetic counseling.